Synthesis and Structural Characterization of (E)-1-(4-Chlorobenzylidene)semicarbazide - Li, Jian (Asian Journal of Chemistry, 2012)
The compound (E)-1-(4-chlorobenzylidene)semicarbazide (C8H8N3OCl, Mr = 197.62) was synthesized and characterized by elemental analysis, IR spectra, 1H NMR spectra and single crystal X-ray diffraction. The crystal belongs to monoclinic, space group P21/c, with a = 17.081(5), b = 4.4508(13), c = 11.896(4) Å, b = 92.979(4)º, V = 903.2(5) Å3, Z = 4, Dc = 1.453 g/cm3, l = 0.71073 Å, μ(MoKa) = 0.384 mm-1, F(000) = 408. The final refinement gave R = 0.0379, wR(F2) = 0.1000 for 1,585 observed reflections with I > 2s(I). X-ray diffraction analysis reveals that the title compound molecule adopts an E configuration about the C=N double bond. The dihedral angles between the semicarbazide group and the benzene ring is 17.4 (2)º. The crystal structure is stabilized by N–H...O hydrogen bonds.